1978
DOI: 10.1212/wnl.28.5.447
|View full text |Cite
|
Sign up to set email alerts
|

Duchenne dystrophy

Abstract: Skinned, single-fiber preparations from the quadriceps or gastrocneumius muscles of four ambulatory male children with Duchenne dystrophy were tested for theri ability to generate tension and to regulate CA++. To determine the intrinsic strength (P0) of the contractile material, the maximum Ca++ -activated tensions were normalized to the fiber diameters. Sixty-four percent of the Duchenne fibers had P0 values below 1.0 kg per square centimeter--the lowest value observed in control muscle--and the average P0 va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

1980
1980
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(18 citation statements)
references
References 0 publications
1
17
0
Order By: Relevance
“…The similarity of Po?cm -2 observed in healthy subjects and patients with COPD does not support the hypothesis that a myopathic process exists in the latter group, since the decrease in strength in this condition would be disproportionately greater than loss in muscle CSA, indicating an impairment of the contractile apparatus [21,22]. At first sight, this result may appear surprising given the common belief that type II fibres, whose proportion is increased in COPD, are stronger than type I fibres.…”
Section: Discussionmentioning
confidence: 91%
“…The similarity of Po?cm -2 observed in healthy subjects and patients with COPD does not support the hypothesis that a myopathic process exists in the latter group, since the decrease in strength in this condition would be disproportionately greater than loss in muscle CSA, indicating an impairment of the contractile apparatus [21,22]. At first sight, this result may appear surprising given the common belief that type II fibres, whose proportion is increased in COPD, are stronger than type I fibres.…”
Section: Discussionmentioning
confidence: 91%
“…In an earlier study, Wood, Sorenson, Eastwood, Charash & Reuben (1978) have shown that 64 % of the DMD fibres developed less tension than the lowest tension (ca 10 N/cm2) measured in normal human fibres. However, these authors could not expand on this observation because the fibre types could not be identified.…”
Section: Normalfibresmentioning
confidence: 86%
“…Importantly, the sarcomeric proteins at the M- and Z-band remain in the skinned fiber in contrast to other reconstituted methods. These experiments measure the Ca 2+ buffering capacities of the myofilament while measuring the development of tension or maximal force [58, 59]. Several groups have also reported differences in the level of basal force (at low Ca 2+ concentrations) after the incorporation of mutant cTnT or cTnI [38, 41].…”
Section: Reconstituted and Structural Assaysmentioning
confidence: 99%